SOFTWARE TOOL FOR CALCULATING THE VOLUME OF THE TETRAHEDRON ON THE LENGTHS OF ITS EDGES - Kuzmich, V.I.; Kuzmich, Y.V. (Journal of Information Technologies in Education (ITE), 2012)
This paper describes the work of the software "calculator" that can be used to calculate the volume of the tetrahedron on the lengths of its edges.